The role of social media in promoting political participation: The Lebanon experience - Muhammad Saud; Dima Bassam el Hariri; Asia Ashfaq (Faculty of Social and Political Science, Universitas Airlangga, 2020)
Social media, as part of the political experience, is an emerging trend in the sociology of youths and politics. The present study aimed to investigate the dynamic role of social media in the context of promoting political participation in Lebanese society. A quantitative survey method was used to collect the data from the field, and a total number of 260 questionnaires were filled in throughout the study. The study suggests that people are openly sharing their political opinions on social media platforms and that their expression rate in terms of sharing and learning political knowledge is increasing. The majority of respondents are using Facebook, Twitter, and Instagram for political purposes. The creation of social media has brought about an innovative advancement when it comes to individuals participating freely for political reasoning. Additionally, with exciting features and the freedom to share videos, pictures, and status updates, social media applications increasingly allow them to participate in political discussions. Where social media is providing opportunities for the public to participate in politics, electronic media is also facilitating a generation in terms of them gaining political knowledge from political talk shows. Social media’s appropriateness for spreading something broad has triggered a contagious phenomenon that allows every notice polled to be accessed by everyone. It is possible to conclude that social media is suitable for use as an online political platform, and it provides an opportunity for the respondents to participate in the political sector of their country.